Model-driven software development technology, engineering, management - Stahl, Thomas (J. Wiley & Sons, 2006)
Model-Driven Software Development (MDSD) is currently a highly regarded development paradigm among developers and researchers. With the advent of OMG's MDA and Microsoft's Software Factories, the MDSD approach has moved to the centre of the programmer's attention, becoming the focus of conferences such as OOPSLA, JAOO and OOP. MDSD is about using domain-specific languages to create models that express application structure or behaviour in an efficient and domain-specific way. These models are subsequently transformed into executable code by a sequence of model transformations. This practical guide for software architects and developers is peppered with practical examples and extensive case studies. International experts deliver: A comprehensive overview of MDSD and how it relates to industry standards such as MDA and Software Factories. Technical details on meta modeling, DSL construction, model-to-model and model-to-code transformations, and software architecture. Invaluable insight into the software development process, plus engineering issues such as versioning, testing and product line engineering. Essential management knowledge covering economic and organizational topics, from a global perspective. Get started and benefit from some practical support along the way!